1985
DOI: 10.1007/bf01655406
|View full text |Cite
|
Sign up to set email alerts
|

Results of surgical treatment of necrotizing pancreatitis

Abstract: In 205 patients with necrotizing pancreatitis, surgery was carried out following failure of medical treatment. Intraoperatively, according to the size of the necrotic area and the weight of the surgically removed necrotic tissue, 79 patients showed a limited panereatic necrosis, and 126 patients an extended necrotizing process. In 40.4% of 138 patients with bacteriological reports, a bacterial contamination of the pancreatic necrosis was found. The main objective of surgical management was the removal of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
7

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(56 citation statements)
references
References 30 publications
(46 reference statements)
1
48
0
7
Order By: Relevance
“…14, 15 Beger et al, 16 in a review of 205 patients undergoing surgery for severe acute pancreatitis, found that the presence and extent of necrosis were the principal determinants of not only the severity of the clinical course but also of overall survival: the risk of death increased with the increased amount of necrosis. In data from surgical and autopsy series, necrotizing pancreatitis accounted for 70% to 86% of the deaths from acute pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…14, 15 Beger et al, 16 in a review of 205 patients undergoing surgery for severe acute pancreatitis, found that the presence and extent of necrosis were the principal determinants of not only the severity of the clinical course but also of overall survival: the risk of death increased with the increased amount of necrosis. In data from surgical and autopsy series, necrotizing pancreatitis accounted for 70% to 86% of the deaths from acute pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are usually severely ill, and pancreatic infection is a common complication, often responsible for the high mortality rate in these patients [2]. Early recognition of patients with pancreatic necrosis by using CT can be helpful in predicting the severity of pancreatitis and in identifying those patients likely to develop pancreatic infection [2,3].…”
Section: January 1991mentioning
confidence: 99%
“…The purpose of this study was to correlate enhancement of pancreatic parenchyma on contrast-enhanced CT with necrosis found surgically in patients with suspected necrotizing pancreatitis. [2,5,6]. Present clinical criteria [4] are useful but imperfect in separating patients with acute (self-limited) edematous pancreatitis from those with necrotizing pancreatitis.…”
Section: January 1991mentioning
confidence: 99%
“…Fluid located in the posterior pararenal or perirenal space was graded higher because this is considered an uncommon finding (19). It is interesting that, although pancreatic glandular necrosis has long been considered a very important radiologic prognostic sign (5,20,21), this input did not improve the performance of the ANN. This is likely because substantial necrosis (ie, Ͼ30%) will be seen in only a small number of consecutive patients with acute pancreatitis.…”
Section: Discussionmentioning
confidence: 99%